PENGARUH LINGKUNGAN KELUARGA DAN LINGKUNGAN PERGAULAN TERHADAP PRESTASI BELAJAR EKONOMI SISWA - Suratno, Suratno (Fakultas Ekonomi, Universitas Negeri Semarang, 2014)
The objective of the study was to analyze the influence of family environment and social environment toward students’ achievement for Economics subject at the XI Social Studies students in SMA N 3 Jambi in the academic year of 2012/ 2013. The data were collected by questionnaire and documentation. Then, the data were analyzed by descriptive analysis and regression. The result of the study showed that simultaneously, family environment and social environment influenced significantly toward students’ achievement for Economics subject at the XI IPS students in SMK N 3 Jambi. In detail, family environment had more dominant influence than social environment to influence students’ achievement.